Prevalence of Opportunistic Infections and Associated Factors in HIV-Infected Men Who Have Sex With Men on Antiretroviral Therapy in Bach Mai Hospital, Hanoi, Vietnam: A Case-Control Study. Issue 3 (June 2020) - Dang, Linh Vu Phuong; Nguyen, Quan Hai; Ishizaki, Azumi; Larsson, Mattias; Vu, Nhung Thi Phuong; Do Duy, Cuong; Olson, Linus; Dinh, Thanh Thi
Objective: To investigate the distribution of opportunistic infections (OIs) and factors associated with acquiring OIs in human immunodeficiency virus (HIV)-infected men who have sex with men (MSM) in comparison to those of heterosexual patients. Method: A cross-sectional study was conducted on 82 HIV-infected MSM and 120 HIV-infected heterosexual men in Bach Mai Hospital, Hanoi, Vietnam. Demographical characteristics and clinical data were collected and analyzed using appropriate statistics (Mann–Whitney, Chi-square, Fisher's exact test, and logistic regression). Results: The prevalence of OIs among MSM and heterosexual patients were 63.4% and 81.7%, respectively. The most frequent OI in the MSM group was human papilloma virus (HPV) (11%), followed by hepatitis B virus (8.5%), mycobacterium tuberculosis (7.3%), and Talaromycosis (2.4%). Conclusions: Multivariate logistic regression analysis showed that buying sex (odds ratio (OR) = 4, 95% confidence interval (CI): 1.13–14.25) and injecting drugs (OR = 13.05, 95% CI: 2.39–71.21) were associated with increased odds of having OIs in heterosexual patients while increasing age (OR = 1.1, 95% CI: 1.01–1.24) was correlated to increased odd of acquiring OIs in the MSM group. HIV-infected MSM accumulates OIs with increasing age, while heterosexual individuals increase opportunistic infections by buying sex or injecting drugs.